Bug and Test Case Tracking: Optimizing Software Quality with Fabric Dashboards - Sampath Kumar Varanasi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Fabric Dashboards revolutionizes software quality management by introducing an integrated approach to bug tracking and test case management. This advanced platform seamlessly combines real-time monitoring, automated issue classification, and predictive analytics to streamline the software development lifecycle. Through a sophisticated multi-layered architecture, it enables organizations to detect and resolve defects efficiently while maintaining comprehensive test coverage across critical system components. The solution incorporates AI-driven features for bug triage, test case generation, and cross-project correlation analysis, significantly enhancing team collaboration and development efficiency. By implementing automated alert mechanisms and intelligent resource allocation strategies, Fabric Dashboards help organizations reduce operational disruptions and minimize the financial impact of software defects. The platform’s mobile monitoring capabilities and advanced visualization tools ensure continuous system oversight, while its scalable architecture accommodates growing development needs. These capabilities, combined with robust integration patterns and optimized performance strategies, transform how development teams approach quality assurance and defect management in modern software development environments.